An Analysis of Dilara’s First Language Acquisition: A Three-Year Child - Nur Azmi Rohimajaya; Welliam Hamer (Journal of English Language Studies, 2020)
The objective of the research was to analyze the first language acquisition on a three years child based on phonological, morphological, and semantic aspects. This research was conducted with descriptive qualitative research where the subject and object were taken from the child at age 3 years old. The researchers took their daughter named Truly Dilara Tenderly Wellaz as the subject and got the data by observation and video recording. Based on the analysis, the researchers concluded that Dilara was able to communicate appropriately. Finally, the parents’ role is important to develop the child language. The parents should build interaction with their children to know their child’s language development. Besides that, the researchers suggest the parents say the right pronunciation to their children